Receptor-Dependent Endocytosis Mediates α-Synuclein Oligomer Transport Into Red Blood Cells - Li, Wei; Hu, Junya; Li, Xin; Lu, Zhe; Li, Xuying; Wang, Chaodong; Yu, Shun (Frontiers in Aging Neuroscience, 2022)
Detection of oligomeric α-synuclein (o-α-Syn) in red blood cells (RBCs) has been shown to be promising in diagnosing Parkinson’s disease and other synucleinopathies. However, if RBC o-α-Syn derive from plasma and can reflect changes of plasma o-α-Syn remains unclear. In this study, synthetic o-α-Syn was intravenously injected into mice and dynamic changes in plasma and RBC o-α-Syn levels were investigated. Injection of o-α-Syn induced a temporary increase in plasma o-α-Syn levels, which then decreased to a relatively stable level. In contrast, levels of RBC o-α-Syn increased steadily and significantly. Besides, α-Syn-immunoreactive particles were observed in RBCs of the injected mice, suggesting that RBCs can actively take up and enrich o-α-Syn from plasma. Moreover, incubation of o-α-Syn with isolated RBCs at concentrations lower than those of endogenous o-α-Syn led to a time- and concentration-dependent o-α-Syn elevation in RBCs, which was impaired by lowering the temperature and treatment with proteinase K. The o-α-Syn accumulation in RBCs was also inhibited by specific inhibitors of receptor-dependent endocytosis, including dynamin-, clathrin-, and caveolae-dependent endocytosis. The above results suggest that plasma o-α-Syn can be actively transported into RBCs via receptor-dependent endocytic pathways.